Health Consequences of Starting a Career on a Fixed-Term Contract - Wolfgang Auer (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2015)
I study the short- to medium-run effects on subsequent health outcomes of starting a career on a fixed-term contract. I focus on career start since I expect that temporary contracts and their inherent economic uncertainty imply a path dependence that might have spill-over effects on other domains of life. The empirical analysis is based on rich data from the German Socio-Economic Panel, which provides comprehensive information about individuals labor market history as well as health conditions. My main results are the following. (i) Women react to fixed-term employment at the beginning of their career by experiencing worse mental health in the short run. This relationship is driven by the subjective perception of stress and pressure in these jobs, fades out over time, and is strongest in the sam-ple of women with secondary education. (ii) Women s physical health is not af-fected at all. (iii) Economic uncertainty due to fixed-term employment has no fu-ture consequences for men s mental or physical health. I argue that these findings are robust to several sensitivity tests as well as to potential endogeneity threats.
Keywords: I31; I12; J41; 330